Ulcerated melanoma: Systems biology evidence of inflammatory imbalance towards pro‐tumourigenicity. (22nd December 2021) - Davies, John; Muralidhar, Sathya; Randerson‐Moor, Juliette; Harland, Mark; O'Shea, Sally; Diaz, Joey; Walker, Christy; Nsengimana, Jérémie; Laye, Jon; Mell, Tracey; Chan, May; Appleton, Lizzie; et al.
Abstract: Microscopic ulceration is an independent predictor of melanoma death. Here, we used systems biology to query the role of host and tumour‐specific processes in defining the phenotype. Albumin level as a measure of systemic inflammation was predictive of fewer tumour‐infiltrating lymphocytes and poorer survival in the Leeds Melanoma Cohort. Ulcerated melanomas were thicker and more mitotically active (with corresponding transcriptomic upregulated cell cycle pathways). Sequencing identified tumoural p53 and APC mutations, and TUBB2B amplification as associated with the phenotype. Ulcerated tumours had perturbed expression of cytokine genes, consistent with protumourigenic inflammation and histological and transcriptomic evidence for reduced adaptive immune cell infiltration. Pathway/network analysis of multiomic data using neural networks highlighted a role for the β‐catenin pathway in the ulceration, linking genomic changes in the tumour to immunosuppression and cell proliferation. In summary, the data suggest that ulceration is in part associated with genomic changes but that host factors also predict melanoma death with evidence of reduced immune responses to the tumour.